2000
DOI: 10.1177/104063870001200406
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Clostridium Difficile and Its Toxins in Equine Feces: Implications for Diagnostic Test Selection and Interpretation

Abstract: Although Clostridium difficile is recognized as a cause of enterocolitis in horses and humans, there has been little work published regarding the lability of C. difficile and its toxins in feces. A significant decrease in recovery of C. difficile from inoculated equine fecal samples occurred during storage. Recovery after storage in air at 4 degrees C decreased from 76% (37/49) after 24 hours to 67% (33/49) at 48 hours and 29% (14/ 49) after 72 hours. In contrast to aerobic storage, 25 of 26 samples stored ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 33 publications
4
55
1
2
Order By: Relevance
“…However, the assays in the current study were conducted according to the manufacturers' specifications. In addition, previous studies examining stool samples from animals observed no toxin degradation during storage at 220 uC (Keessen et al, 2011;Weese et al, 2000). Another possibility is that the toxins were diluted by the increased volume of stool produced during diarrhoea.…”
Section: Discussionmentioning
confidence: 95%
“…However, the assays in the current study were conducted according to the manufacturers' specifications. In addition, previous studies examining stool samples from animals observed no toxin degradation during storage at 220 uC (Keessen et al, 2011;Weese et al, 2000). Another possibility is that the toxins were diluted by the increased volume of stool produced during diarrhoea.…”
Section: Discussionmentioning
confidence: 95%
“…Exclusion of enrolment of the organism is equally challenging as sample handling requires meticulous attention. Survival of C. difficile rapidly declines within 48-72h if samples, stored at 4°C, are exposed to air (Weese et al 2000). Although the toxins are more resistant and can be recovered even from samples stored aerobically at 4°C for at least 30d, a single toxin negative sample, particularly if taken early in the disease process may not be sufficient to rule involvement of toxigenic C. difficile out (Arroyo et al 2004, Weese et al 2000.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…Survival of C. difficile rapidly declines within 48-72h if samples, stored at 4°C, are exposed to air (Weese et al 2000). Although the toxins are more resistant and can be recovered even from samples stored aerobically at 4°C for at least 30d, a single toxin negative sample, particularly if taken early in the disease process may not be sufficient to rule involvement of toxigenic C. difficile out (Arroyo et al 2004, Weese et al 2000. Equally, culture and toxin may rapidly become negative within 48-72h after initiation of treatment with metronidazole (Arroyo et al 2004).…”
Section: Clostridium Difficilementioning
confidence: 99%
“…Die bakterielle Kultivierung des C. difficile gestaltet sich schwieriger und Untersuchungen mehrerer Kotproben können hierfür nötig werden (Jones 1989, Marler et al 1992). Die Detektion der Toxine A und B über Immunassays, zellzytotoxische Assays oder eine PCR, zum Nachweis der für die Toxinbildung verantwortlichen Gene des Bakteriums, stellen sensitivere Methoden dar (Jones 2000, Weese et al 2000, Jones 1989). (Mackenthun et al 2013).…”
Section: Introductionunclassified